A dengue está por perto? Uma análise investigativa sobre as potencialidades do risco de transmissão da dengue em localidades próximas a uma escola pública de Belo Horizonte - Davidson Rogério Gonçalves Conceição (2024)
Dengue is a disease that has been part of people's daily lives throughout the country. This situation is directly related to the transmitter which, in the urban environment, is increasingly adapted to environmental conditions, many of which are provided by human beings themselves. The Aedes aegypti mosquito, the main vector of dengue fever, found an appropriate place in the urban environment to develop its life cycle. There is no shortage of places for egg deposition, larvae development and feeding, whether hematophagous or not. This study was developed with students in the third year of high school, in a state public school in the city of Belo Horizonte, located in the North Region of this city. This region, historically, according to data made available by the local city hall, occupies a relevant place when looking at the number of confirmed or suspected cases of dengue infection. The proposed didactic sequence was developed through an investigative approach, using active methodologies. By exploring and observing the environment where they live, students were able, through initial questioning, to develop the stages of scientific work. The evolution of the work stages included the collection of photographic records, preparation and application of questionnaires, development of graphs and tables. There was also the use of digital tools, which until then were little known to these students. Thus, in addition to acquiring new skills, students were able to conclude that the region close to the school is, in fact, conducive to dengue transmission. This was possible after analyzing the graphs and tables generated from the records of dengue cases made available by municipal health agencies, and the evidence collected from observations of locations close to the school. Photographic evidence supported the hypotheses that the trash accumulated in neighboring streets and places that constantly accumulate water are, among others, fundamental factors for this transmission. Responses collected through a questionnaire that probed information about the number of people infected with dengue and other diseases transmitted by Aedes aegypti, also showed the occurrence of cases in the vicinity of the school. In addition to the didactic sequence itself, a game was created with part of the evidence collected. These aim to contribute to future environmental education actions.